Study of factors leading to cancellation of elective surgeries in a tertiary care hospital - Verma, Surender; Gaurav Kumar,; Sunil Kumar Yadav,; Anjali Verma,; Simon Seiwa Lanah L, (Asian Journal of Medical Sciences, 2024)
Background: The postponement of elective surgeries is a major problem that increases the time for patients on surgical waiting lists and can negatively affect psychologically and physically to patients and their families. Cancellation rates reported within the literature are highly variable with considerable differences depending on type of hospital, national health care systems or policies, geographical region, patient population, providers, and also the perioperative management practices present at specific institution. Aims and Objectives: The current study was to thoroughly understand the causes to minimize such cancellations in our institute. Materials and Methods: A prospective observational study was conducted in the Department of General Surgery in a tertiary care teaching hospital in North India. All the patients admitted for elective surgeries in the Department of General Surgery over a period of December 1st, 2022–May 30th, 2023 were noted and out of them, details of patients in whom surgery was cancelled were taken and they were followed for 2 months. Results: Out of a total 1065 patients, 92 patients got cancelled during the study period. Out of them, 67 patients (67.8%) were cancelled on the scheduled date of surgery or after reaching operation theatre whereas, 25 patients (27.2%) were cancelled on day before scheduled date of surgery. Maximum number of cancelled patients were of cholelithiasis planned for laparoscopic cholecystectomy followed by inguinoscrotal swellings. Maximum number of patients were deferred due to administrative-related factors, followed by medical related factors. Conclusion: This study will act as a quality improvement initiative by reducing the surgery cancellation rate thus improving utilization of limited resources and valuable time to provide better health care services in our institute. Such cancellations can be minimized by better planning and active inter-departmental communication regarding proposed plan of surgery.